Discursive genres in tourism. Analysis of web pages of institutional tourism promotion - Pillajo Borja, Hernán Patricio (Tierra Infinita, 2019)
In the last forty years, the teaching of reading and writing, now known by various authors as literacy, has evolved significantly and went from strictly linguistic approaches, tocognitive approaches and in the last decade to be studied by the socio-cultural current. Thus, under this last model we no longer speak of simple texts but of discursive genres, that the use of the language takes place in the form of both spoken and written texts that respond to a specific context, time and space. As in other professions, tourism has a form of communicationmaterialized in specific discursive genres of wide heterogeneity, which respond to a social context, a historical moment and a specific space. One of these genres is the web page, part of a macro-genome called institutional that which originates in official organisms with the purpose of strengthening or positioning the image of a tourist destination. How all discursive genre web pages respond to an intentionality and develop a purpose that must be clearly reflected in its contents. The present work analyzes the institutional webs of tourist promotion of the municipalities of Quito, Guayaquil, Cuenca and San Cristobal, with the purpose of establishing their discursive particularities and if they correspond to the categorization of tourist genre previously described.
Keywords: Gender; tourism promotion